ANALISIS REGRESI KEJADIAN KEHAMILAN RISIKO TINGGI DALAM PERSPEKTIF PENDIDIKAN. PENGETAHUAN DAN SIKAP IBU HAMIL - Lilik Triyawati; Sri Wahyuni; Yaimin; Masfuah Ernawati (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2025)
Background High-risk pregnancy is a condition that can affect the condition of the mother and fetus in the pregnancy at hand. High-risk pregnancy does not occur suddenly because pregnancy and its effects on the organs of the body take place gradually and gradually. The purpose of this study was to analyze the incidence of high-risk pregnancies in the perspective of education, knowledge and attitudes of pregnant women at the Puskesmas. The sample in this study were some pregnant women in the area of ??Puskesmas Kanor Bojonegoro as many as 88 respondents who were taken by simple random sampling technique.The independent variable is education, knowledge, attitude of pregnant women, while the dependent variable is the incidence of high risk pregnancy. Collecting data with questionnaires and secondary data.Data analysis with regression test with a significance level of 0.05. Discussion Analyzing the education,knowledge,attitudes,the dominant factors associated with the incidence of high risk pregnancies. The results of this study indicate that the dominant factor associated with the incidence of high-risk pregnancy is knowledge with a value of B = 0.260 indicating that there is a relationship between knowledge and the incidence of high-risk pregnancy, p value = 0.000.There is a relationship between the attitude of pregnant women with the incidence of high-risk pregnancy with a value of B = 0.326 (p value = 0.005). There is a relationship between education value B = 0.155 (p value = 0.035) with the incidence of high risk pregnancy.Recommendations for pregnant women, the government and for future researchers.